HUBUNGAN STRATEGI PEMBELAJARAN GURU DAN KEAKTIFAN SISWA TERHADAP HASIL BELAJAR MATA PELAJARAN SENI BUDAYA DI SMP PEMBANGUNAN LABORATORIUM UNP PADANG - VUTRA PERMATASARI, Drs. Yusron Wikarya, M.Pd., Drs. Eswendi, M.Pd. (Serupa The Journal of Art Education, 2019)
The purposes of this study was to find out (1) the relationship between teacher learning strategies and student learning outcomes in Cultural Arts subjects at the Middle School Development of the UNP Padang Laboratory. (2) Relationship between student activity and student learning outcomes in Cultural Arts subjects at the Middle School Development of the UNP Padang Laboratory. (3) Relationship between teacher learning strategies and activeness of students with student learning outcomes in Cultural Arts subjects at the Middle School Development of the UNP Padang Laboratory. The method of this research is correlational descriptive research. Data is collected using a document format used for student learning outcomes, then questionnaires to collect data about teacher learning strategies and student activity. The results of the study are that there is a significant relationship between teacher learning strategies and learning outcomes of 14.82%, there is a significant relationship of student activity with student learning outcomes of 95.45%, there is a significant relationship between learning strategies and student activity with learning outcomes of 95 , 84% at 95% confidence level.Keywords: Learning Strategy, Activity, Learning Outcomes